1995
DOI: 10.1111/j.1550-7408.1995.tb05901.x
|View full text |Cite
|
Sign up to set email alerts
|

Ceratomyxa sparusaurati N. Sp. (Myxosporea: Bivalvulida), a New Parasite from Cultured Gilthead Seabream (Sparus aurata L.) (Teleostei: Sparidae): Light and Electron Microscopic Description

Abstract: ABSTRACT. A new Myxosporea, Ceratomyxa sparusaurati n. sp., was found in the gall bladder and bile of cultured gilthead sea bream (Sparus aurata L.) from different Spanish fish farms. It is clearly different from all the previously reported Ceratomyxa from sparids, and it is distinguished from other members of the genus by the shape and size of the spores. Prevalence of infection was 2.15% in an Atlantic farm, 48.7% in a Mediterranean farm and 28.6% in the facilities of the Instituto de Acuicultura de Torre d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…A similar interaction was observed in Myxidium trachinorum, which contacts the epithelium of the gall bladder through two to three filose processes (Canning et al 1999). At one end of some primary cells, rhizoid-like projections were observed in Ceratomyxa sparusaurati (Sitjà-Bobadilla et al 1995). Unlike in this last species, in C. tenuispora we did not see any contact with epithelial cells of the gall bladder and the shape and distribution of the cytoplasmic projections found in C. tenuispora show some ultrastructural differences.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…A similar interaction was observed in Myxidium trachinorum, which contacts the epithelium of the gall bladder through two to three filose processes (Canning et al 1999). At one end of some primary cells, rhizoid-like projections were observed in Ceratomyxa sparusaurati (Sitjà-Bobadilla et al 1995). Unlike in this last species, in C. tenuispora we did not see any contact with epithelial cells of the gall bladder and the shape and distribution of the cytoplasmic projections found in C. tenuispora show some ultrastructural differences.…”
Section: Discussionmentioning
confidence: 67%
“…Only some species were ultrastructurally studied, such as C. shasta (Yamamoto and Sanders 1979), C. globulifera (Desportes and Théodoridès 1982), Ceratomyxa sp. hyperparasitized with the microsporidian Nosema ceratomyxae (Diamant and Paperna 1989), C. labracis and C. diplodae (Alvarez-Pellitero and Sitjà-Bobadilla 1993, Sitjà-Bobadilla and AlvarezPellitero 1993a), C. sparusaurati (Sitjà-Bobadilla et al 1995, Palenzuela et al 1997, C. drepanopsettae (Morrison et al 1996), and C. protopsettae (Cho et al 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some fish were a#ected by a mild to moderate microcotylid gill infection. Ceratomyxa was observed in the gallbladder following the description made by Sitjà -Bobadilla et al (1995) HISTOPATHOLOGY In most samples (76%), a substantial increase in the number of mucous cells was recognised in the epithelium of the gut (Fig. 2a).…”
Section: Gross Pathologymentioning
confidence: 95%
“…In the present study, we found another Ceratomyxa species, C. sparusaurati, from the gallbladder of rock bream. C. sparusaurati was first reported from gilthead sea bream (Sparus aurata) in the Mediterranean by Sitjà-Bobadilla et al (1995), and is known to be able to provoke inflammatory reactions and histopathological damage such as vacuolization, sloughing, and detachment of epithelial cells (Palenzuela et al 1997). In the present study, we investigated the morphological and ultrastructural characteristics of C. sparusaurati using light and transmission electron microscopy (TEM).…”
Section: Members Of the Genus Ceratomyxamentioning
confidence: 99%